Peran Kekuatan Karakter terhadap Resiliensi Wartawan - Putri, Mitha Adisty; Mawarpury, Marty; Dahlia, Dahlia; Iriamanda, Irin (Intuisi : Jurnal Psikologi Ilmiah, 2023)
Wartawan seringkali berhadapan dengan berbagai tantangan dan risiko ketika melakukan kegiatan jurnalistik sehingga memerlukan kemampuan resiliensi untuk dapat bertahan. Salah satu faktor untuk mengembangkan resiliensi adalah kekuatan karakter. Penelitian ini bertujuan untuk mengetahui peran kekuatan karakter terhadap resiliensi wartawan di Aceh. Sejumlah 168 wartawan yang tergabung dalam Persatuan Wartawan Indonesia (PWI) Aceh menjadi subjek penelitian melalui metode total sampling. Penelitian menggunakan alat ukur Connor Davidson Resilience Scale (CD-RISC) 25 yang diadaptasi dari Ramadhan (2018) dan Virtues in Action (VIA) 72 Scale-short dari VIA Institut. Analisis data menggunakan simple linear regression analysis dengan hasil penelitian menunjukkan bahwa kekuatan karakter memiliki peran yang signifikan terhadap resiliensi wartawan (R2 = .367, β1 = .781, p = .000; ≤.05). Kekuatan karakter yang berperan signifikan terhadap resiliensi yaitu curiosity, social intelligence, dan hope. Selain itu, kekuatan karakter dominan yang dimiliki wartawan Aceh yaitu hope, forgiveness, dan appreciation of beauty and excellent. Journalists are often faced with various challenges and risks when carrying out journalistic activities, so they need resilience skills to survive. One factor in developing resilience is character strength. This study aims to determine the role of character strength in the resilience of journalists in Aceh. A total of 168 journalists who were members of the Indonesian Journalists Association (PWI) in Aceh were included in the study using the total sampling method. The study used the Connor Davidson Resilience Scale (CD-RISC) 25 adapted from Ramadhan (2018) and the Virtues in Action (VIA) 72 Scale-short from the VIA Institute as the measurement tools. The data were analyzed using simple linear regression analysis, and the results showed that character strength significantly contributed to the resilience of journalists (R2 = .367, β1 = .781, p = .000; ≤.05). The character strengths of curiosity, social intelligence, and hope were found to have a significant impact on the resilience of journalists. Moreover, the dominant character strengths among journalists in Aceh were found to be hope, forgiveness, and appreciation of beauty and excellence Journalists are often faced with various challenges and risks when carrying out journalistic activities, so they need resilience skills to survive. One factor in developing resilience is character strength. This study aims to determine the role of character strength in the resilience of journalists in Aceh. A total of 168 journalists who were members of the Indonesian Journalists Association (PWI) in Aceh were included in the study using the total sampling method. The study used the Connor Davidson Resilience Scale (CD-RISC) 25 adapted from Ramadhan (2018) and the Virtues in Action (VIA) 72 Scale-short from the VIA Institute as the measurement tools. The data were analyzed using simple linear regression analysis, and the results showed that character strength significantly contributed to the resilience of journalists (R2 = .367, β1 = .781, p = .000; ≤.05). The character strengths of curiosity, social intelligence, and hope were found to have a significant impact on the resilience of journalists. Moreover, the dominant character strengths among journalists in Aceh were found to be hope, forgiveness, and appreciation of beauty and excellence.